POLA SPASIAL DAN TEMPORAL DAERAH PENANGKAPAN IKAN PELAGIS MENGGUNAKAN DATA OSEANOGRAFI DI PERAIRAN SUMATERA BARAT - Mutiara Alkayakni Harahap; Vincentius Paulus Siregar; Syamsul Bahri Agus (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
The West Sumatera waters is one of the waters that has a huge potential for fish resources. Many fishing activities carried out near the coast, and fishing gear used in West Sumatra waters is a Bagan. This study aims to determine the relationships between sea surface temperature and Chl-a concentration with pelagic fish catches in West Sumatera waters. The data used were SST and Chl-a in the periode of 2014 – 2016. The variability of SST and Chl-a data was analyzed using Empirical Orthogonal Function (EOF) method. This study shows that the EOF SPL mode indicates that the overall value of SPL range is above the average (positive anomaly) with a total variance of 81.24%, while the Chl-a shows that the overall value of variability is at an average (negative anomaly) variance of 70.23%. The results of cross-correlation between SPL and pelagic fish have a lag time of 2.2 months, meaning that pelagic fish predates SST and predominantly occurs in a 6-month period. The relationship between Chl-a and pelagic fish was dominant in the 0.5 year period which showed a gap between Chl-a and pelagic fish catches with a lag time of 22 days.